COMBINED EFFECT OF EXERCISE THERAPY AND ELECTRO THERAPEUTIC MODALITY ON SHOULDER HAND SYNDROME IN STROKE PATIENTS - R Vispute, Ankeeta; B. Kanase, Suraj (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: The objectives of the study are to evaluate the effect of hot moist packs with exercises and transcutaneous electrical nerve stimulation(TENS) with exercises and investigate the effect of hot damp packs with exercises and transcutaneous electrical nerve stimulation with exercises on shoulder-hand condition in stroke subjects.Methods: Ethical clearance was obtained from the ethical committee, KIMSDU, Karad. The study was conducted at the Physiotherapy Department of KIMSDU. A comparative study was done on a total of 40 subjects. they were equally divided into two groups using simple random sampling withottery method (Group A and Group B) Group A was given a hot, moist pack with exercises, and Group B was given transcutaneous electrical nerve stimulation with exercises.Result: Statistical analysis was performed using paired t-tests and unpaired t-tests. In pre-intervention, there was no statistically significant difference seen according to p-values for Voluntary Control Grade (VCG) 0.7436, Visual Analogue Scale (VAS) 0.6092, and Shoulder Pain and Disability Index (SPADI) 0.8487 . On comparing the post-interventional values, the results between the two groups using unpaired t-test showed that there was extremely significant difference seen in p value for Voluntary control grade (VCG) 0.0002 Visual analogue scale (VAS) 0.0001 likewise, for Shoulder Pain and Disability Index (SPADI) 0.0001Conclusion: The study concluded that thatTranscutaneous electrical nerve stimulation (TENS) and exercises are significantly effective in reducing pain and improving voluntary control in subjects with shoulder-hand syndrome.